Employing Artificial Intelligence in Producing Media Content in Jordanian TV Channels - Alabed Alrahman, Abdelbaset Ahmad (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aimed to determine the degree of utilization of artificial intelligence (AI) techniques in producing media content on Jordanian television channels, the areas of their application, and the factors influencing their adoption. Method: A survey method was employed, targeting media professionals from Roya TV, Al-Mamlaka TV, and Jordan TV, using an equal quota sample of 210 individuals. Results: The findings revealed that Jordanian TV channels show significant interest in AI technology and actively use it in media content creation. Fixing linguistic and spelling issues emerged as a primary application of AI. Additionally, AI technologies were found to enhance creativity and innovation in media production, with advanced computers and Internet servers forming the backbone of infrastructure. Channels anticipated using AI to access data and information more efficiently. Social encouragement among colleagues played a significant role in AI adoption, while workers’ lack of experience with AI-based visual content creation posed a notable challenge. Conclusion: The study recommends that Jordanian television channel administrations organize training workshops to equip employees with AI usage skills in media production. Furthermore, providing advanced technical infrastructure, such as virtual studios, is essential due to its cost-effectiveness and ability to save time and effort.